2020
DOI: 10.14411/eje.2020.009
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour of Scymnus syriacus (Coleoptera: Coccinellidae) provided with Aphis spiraecola and Aphis gossypii (Hemiptera: Aphididae) as prey: Functional response and prey preference

Abstract: http://www.eje.cz Citrus tristeza closterovirus (Closterovirus: Closteroviridae) (Ayazpour et al., 2013). Chemical control is the main method used to control citrus aphids (Smaili et al., 2014). However, excessive use of insecticides reduces natural enemy populations and leads to resistance of the aphids to many common insecticides. Biological control is a safe alternative method for controlling aphids in citrus orchards (Alizadeh Kafeshani et al., 2018).Scymnus syriacus Marseul (Coleoptera: Coccinellidae) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The expected increase in metabolic rates with warming are associated with greater energy demands, which should cause predators to increase food intake and foraging activity. Determining these parameters with respect to phenological stage confirmed poor response by the first three instars as reported earlier 59 , 74 , whereas increased foraging performance by final instar and adult H. axyridis (especially female when compared with male) 24 , 45 , 52 suggesting H. axyridis may provide better biocontrol efficiency at later stages, plausibly owing to better searching efficiencies. The 4th instar requires large meals to attain the required weight for pupation 75 and adult predators have to prepare for reproduction 56 and other functions related to egg maturation or fertilization 76 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The expected increase in metabolic rates with warming are associated with greater energy demands, which should cause predators to increase food intake and foraging activity. Determining these parameters with respect to phenological stage confirmed poor response by the first three instars as reported earlier 59 , 74 , whereas increased foraging performance by final instar and adult H. axyridis (especially female when compared with male) 24 , 45 , 52 suggesting H. axyridis may provide better biocontrol efficiency at later stages, plausibly owing to better searching efficiencies. The 4th instar requires large meals to attain the required weight for pupation 75 and adult predators have to prepare for reproduction 56 and other functions related to egg maturation or fertilization 76 .…”
Section: Discussionsupporting
confidence: 77%
“…Our results of greater predation by the 4th instar and female H. axyridis are supported by previous reports investigating the functional response of coccinellids, namely Adalia tetraspilota (Hope), Hippodamia variegata (Goeze), Harmonia dimidiata (Fab. ), and Scymnus syriacus Marseul preying on many aphid species 44 , 45 , 77 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of Scymnus larvae has been reported to be effective in controlling Aphis gossypii (Bouvet et al 2019). Larvae of Scymnus syriacus performed higher predation capacity than their male and female imagoes (Moradi et al 2020). According to Hamback et al (2021), third instar larvae of Scymnus had highest predation capacity compared to the other stadia of predator.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the response type was Type-II. In addition, it has been observed that especially the late larvae and adults of the predator insect have a high attack rate on both foods in a short time (Moradi et al, 2020). In a study on Bemicia tabaci (Hemiptera: Aleyrodidae) eggs of different densities, the functional response of Delphastus catalinae and D. pallidus (Coleoptera:…”
Section: Numerical Response Of Hippodamia Variegatamentioning
confidence: 99%